2017
DOI: 10.1007/s12011-017-1012-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Agaricus blazei Murill Polysaccharide on Cadmium Poisoning on the MDA5 Signaling Pathway and Antioxidant Function of Chicken Peripheral Blood Lymphocytes

Abstract: This experimental study investigated the effect of Agaricus blazei Murill polysaccharide (ABP) on cadmium (Cd) poisoning on the melanoma differentiation-associated gene 5 (MDA5) signaling pathway and antioxidant function of peripheral blood lymphocytes (PBLs) in chickens. The experiments were divided into four groups: 7-day-old chickens with normal saline (0.2 mL single/day), Cd (140 mg/kg), ABP (30 mg/mL, 0.2 mL single/day), and Cd + ABP(140 mg/kg/day + 0.2 mL ABP). Peripheral blood was collected on the 20th,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Zhang et al observed that Sargassum polysaccharide inhibited oxidative stress induced by infectious bursa disease virus in bursal lymphocytes of chickens [50]. Lv et al found that a polysaccharide from Agaricus blazei Murill had antioxidant effect in chicken peripheral blood lymphocytes treated with cadmium [51]. In this study, Rg1 significantly reduced oxidative stress-induced apoptosis and damage of chicken lymphocytes.…”
Section: Discussionmentioning
confidence: 50%
“…Zhang et al observed that Sargassum polysaccharide inhibited oxidative stress induced by infectious bursa disease virus in bursal lymphocytes of chickens [50]. Lv et al found that a polysaccharide from Agaricus blazei Murill had antioxidant effect in chicken peripheral blood lymphocytes treated with cadmium [51]. In this study, Rg1 significantly reduced oxidative stress-induced apoptosis and damage of chicken lymphocytes.…”
Section: Discussionmentioning
confidence: 50%
“…Ethical treatment of animals used in this study was approved by the Animal Welfare Committee protocol (#NEAU-2013-02-0252-11) at Northeast Agricultural University (Harbin, China) Anticoagulant blood samples were dissected from 15-day-old Hyline egg-laying chickens (Harbin, China), and carefully placed in a tube containing lymphocyte in a separation medium (Tian Jin Hao Yang Biological Manufacture Co. Ltd., Tianjin, China), and the specific extraction method of chicken PBLs was routine procedure in our laboratory [ 12 ]. The acquired cells were cultured in a 37 °C 5% CO 2 incubator for 24 h. The APS were extracted from Astragalus by the Sevag method according to our previous study [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The protein samples were separated using 8% sodium dodecyl sulfate polyacrylamide gel electrophoresis and then transferred to nitrocellulose membrane. The membrane was blocked using skim milk (5%) and then incubated with the primary antibody of MDA5 [ 12 ] (1:1000) at 4 °C overnight, followed by incubation with horseradish peroxidase-conjugated goat anti-mouse immunoglobulin (Ig)G (1:5000, Beijing Solarbio Science & Technology Co., Ltd., Beijing, China) for 1 h after washing three times. At the same time, the membrane was incubated with the β-actin antibody (1:1000, Beijing Zhong Shan-Golden Bridge Biological Technology Co., Ltd., Beijing, China) followed by incubation with horseradish peroxidase-conjugated goat anti-mouse IgG (1:5000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agaricus blazei Murill (AbM), known in China as jisongrong, is widely planted for its value as a food source and for its potential application in healthy protection [19,20] . The polysaccharides extracted from AbM exhibited various biological activities, such as regulating cellular immunity and providing antioxidative, antiatherosclerotic, antitumor, anti‐infective and anti‐inflammatory effects [27–31] . The activity of AbM polysaccharides is guided by substances such as the branched β‐1,3‐/1,6‐glucans and proteoglycans [32–36] .…”
Section: Introductionmentioning
confidence: 99%